Tinjauan Hukum Terhadap Penolakan Permohonan Pembatalan Perjanjian Perdamaian PT Anugerah Suryo Propertindo (Studi Putusan Nomor 8/Pdt.Sus- Pembatalan Perdamaian/2024/ PN.Niaga.Jkt.Pst) - Dharmasetya, Lani (PT Elaborium Elevasi Indonesia, 2025)
PT Anugerah Suryo Propertindo has submitted a request for cancellation of the peace agreement by PT Pembangunan Daerah Kalimantan Selatan Perseroda because it has been negligent in implementing the peace agreement (homologation) but the panel of judges in Decision Number 8/Pdt.Sus-Cancellation of Peace/2024/PN.Niaga.Jkt .Pst PT Anugerah Suryo Propertindo has submitted a request for cancellation of the peace agreement by PT Pembangunan Daerah Kalimantan Selatan Perseroda because it has been negligent in implementing the peace agreement (homologation) but the panel of judges in Decision Number 8/Pdt.Sus-Cancellation of Peace/2024/PN.Niaga.Jkt .Pst refused on the grounds that there were no facts or circumstances that were simply proven. The formulation of this research problem is how the Bankruptcy Law and PKPU regulate Peace Agreements, Cancellation of Peace Agreements and whether the rejection of the request for cancellation of the peace agreement by the Panel of Judges in Decision 8/Pdt.Sus-PebatalanPeace/2024/Pn.Niaga.Jkt.Pst is appropriate with the Bankruptcy Law and PKPU. This research uses normative legal research with secondary data. The nature of the research is descriptive and conclusions are drawn deductively. The results of this research consider that the Panel of Judges rejected the request for annulment of this settlement on the grounds that it was not proven, simply because this was a mistake because the application for cancellation of the peace submitted had fulfilled Article 170 paragraph (1) of the Bankruptcy Law and PKPU. In the future, the Panel of Judges will pay more attention and uphold it. legal certainty so that it can guarantee legal certainty and justice for all parties